Synthesis H-Zeolite catalyst by impregnation KI/KIO3 and performance test catalyst for biodiesel production. Issue 1 (January 2016) - Widayat, W.; Wicaksono, Adit Rizky; Firdaus, Lukman Hakim; Okvitarini, Ndaru
Abstract: The objective of this research is to produce H-catalyst catalyst that was impregnated with KI/KIO3 . The catalyst was analyzed about surface area, X-Ray Diffraction (XRD) and performance test of catalyst for biodiesel production. An H-Zeolite catalyst was synthesized from natural zeolite with chemical treatment processing, impregnation KI/KIO3 and physical treatment. The results shows that the surface area of the catalyst by 27.236 m 2 /g at a concentration of 5% KI. XRD analysis shows peak 2-θ at 23.627 o indicating that KI was impregnated on H-zeolite catalyst. The catalyst was tested in production of biodiesel using palm oil with conventional methods for 3 hour at temperature of 70-80 o C. The result for conversion Fatty Acid Methyl Ester (FAME) reached maximum value on 87.91% under production process using catalyst 5% KIO3 -H zeolite.